Risk Management at PT. BQC - Mubarak, Husni; Murtaqi, Isrochmani (The Indonesian Journal of Business Administration, 2014)
Abstract— Generally, every company is expected to initially identify any risk that has been or is likely to occur, then to analyze them and find the best solution. Such process is called risk management. In this case, the use of the framework AUS / NZ 4360 is an approach to manage the risks in PT BQC. Assessing PT BQC’s risks from five categories, namely business, human resource, finance, marketing, and operation, 21 risks are identified. From those identified risks, it is found that at least 3 risks have the highest links with other risks, which are risk of organizational structure, risk of compensation, and liquidity risk. Besides that, risk of survey, risk of employee crime, risks of conflict of interest, risk of bribery, and risk of saturated market are also crucial for the company to be analyzed. Therefore, mitigation of these risks is expected to be an impact on lessening the impact and likelihood of other risks associated. The solutions to mitigate three risks that have the highest links are: restructuring the organization in the branch and clarifying each position’s job description, recalculating the wages using combination of basis (base salary using person-based calculation and work allowance using job-based calculation), adding long-term debt for financing. The risk mitigations for the other catastrophic risks are: updating the survey criteria, using integrity test procedure and investigating directly to the field, conducting evaluation of supplier performance, emphasizing giving credit for productive goods or on productive sectors. Keyword: risk management, PT BQC, AUS/NZ 4360